Christensenella minuta, a new candidate next-generation probiotic: current evidence and future trajectories - Ignatyeva, Olga; Tolyneva, Darya; Kovalyov, Aleksandr; Matkava, Lorena; Terekhov, Mikhail; Kashtanova, Daria; Zagainova, Anzhelika; Ivanov, Mikhail; Yudin, Vladimir; Makarov, Valentin; Keskinov, Anton; Kraevoy, Sergey; et al. (Frontiers in Microbiology, 2024)
Background. As the field of probiotic research continues to expand, new beneficial strains are being discovered. The Christensenellaceae family and its newly described member, Christensenella minuta, have been shown to offer great health benefits. We aimed to extensively review the existing literature on these microorganisms to highlight the advantages of their use as probiotics and address some of the most challenging aspects of their commercial production and potential solutions. Methods. We applied a simple search algorithm using the key words “Christensenellaceae” and “Christensenella minuta” to find all articles reporting the biotherapeutic effects of these microorganisms. Only articles reporting evidence-based results were reviewed. Results. The review showed that Christensenella minuta has demonstrated numerous beneficial properties and a wider range of uses than previously thought. Moreover, it has been shown to be oxygen-tolerant, which is an immense advantage in the manufacturing and production of Christensenella minuta-based biotherapeutics. The results suggest that Christensenellaceae and Christensenella munita specifically can play a crucial role in maintaining a healthy gut microbiome. Furthermore, Christensenellaceae have been associated with weight management. Preliminary studies suggest that this probiotic strain could have a positive impact on metabolic disorders like diabetes and obesity, as well as inflammatory bowel disease. Conclusion. Christensenellaceae and Christensenella munita specifically offer immense health benefits and could be used in the management and therapy of a wide range of health conditions. In addition to the impressive biotherapeutic effect, Christensenella munita is oxygen-tolerant, which facilitates commercial production and storage.